2004
DOI: 10.1523/jneurosci.4880-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Prefrontal Cortex in Memory Storage for Trace Fear Conditioning

Abstract: The prefrontal cortex has been shown to participate in the association of events separated by time. However, it is not known whether the prefrontal cortex stores the memory for these relationships. Trace conditioning is a form of classical conditioning in which a time gap separates the conditioned stimulus (CS) from the unconditioned stimulus (US), the association of which has been shown to depend on prefrontal activity. Here we demonstrate that inhibition of extracellular signal-regulated kinase (Erk) cascade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(155 citation statements)
references
References 48 publications
8
144
1
2
Order By: Relevance
“…In contrast, paired conditioning only induced a transient early wave of ERK1/2 and CREB activation immediately post-training. Our results are congruent with data showing with different behavioral paradigms a learninginduced activation of ERK1/2 (Atkins et al 1998;Blum et al 1999;Cammarota et al 2000;Sananbenesi et al 2002;Runyan et al 2004;Wang et al 2004) in hippocampus. Considering that these studies revealed different time courses of activation, we cannot ascertain that the early activation we found in both conditioning protocols is driven by common molecular mechanisms.…”
Section: Learning and Memory 353supporting
confidence: 93%
“…In contrast, paired conditioning only induced a transient early wave of ERK1/2 and CREB activation immediately post-training. Our results are congruent with data showing with different behavioral paradigms a learninginduced activation of ERK1/2 (Atkins et al 1998;Blum et al 1999;Cammarota et al 2000;Sananbenesi et al 2002;Runyan et al 2004;Wang et al 2004) in hippocampus. Considering that these studies revealed different time courses of activation, we cannot ascertain that the early activation we found in both conditioning protocols is driven by common molecular mechanisms.…”
Section: Learning and Memory 353supporting
confidence: 93%
“…Trace fear conditioned learning requires an intact medial prefrontal cortex, ACC, and hippocampus (Huerta et al, 2000;Blank et al, 2003;Han et al, 2003;Runyan et al, 2004). Consistent with the defect in trace fear conditioning seen in FMR1 KO mice, patients with fragile X syndrome have abnormal activation patterns in the ventromedial prefrontal cortex, ACC, and hippocampus (Menon et al, 2004).…”
Section: Discussionmentioning
confidence: 66%
“…Although several previous studies have suggested a role for the mPFC in memory consolidation, including inhibitory avoidance (43,44), it is unclear whether glucocorticoid administration induces a local memory trace in the mPFC or whether manipulation of the mPFC modulates memory consolidation via interactions with other brain regions. As indicated above, findings of several electrophysiological and behavioral studies indicate that there are reciprocal connections between the mPFC and BLA (10,12,16) that regulate affect and memory (3,11,14).…”
Section: Discussionmentioning
confidence: 99%